Functional and molecular characterization of potential oncogene Sharpin - Khan, Meraj Hasan (fi=Turun yliopisto|en=University of Turku|, 2018)
Sharpin (SHANK‐Associated RH Domain Interactor) is a multifunctional adaptor protein that interacts with other proteins and regulates their functions. For example, Sharpin is a subunit of the linear ubiquitination assembly complex (LUBAC), which promotes NF‐κB activity. Sharpin also acts as a negative regulator of PTEN, integrins, T cell receptor and Caspase 1. In this thesis, I report the first interactome of Sharpin. The interactome identified many novel Sharpin interactors and suggested several new pathways regulated by Sharpin. In addition, I confirmed the direct interaction of Sharpin with the Arp2/3 complex, several members of which were in the Sharpin interactome. Importantly, this interaction is physiologically relevant as Arp2/3‐dependent lamellipodia formation and cell migration are significantly affected if this interaction is hampered. Previously, Sharpin had been reported to be essential for the last step of granulocyte transmigration; the release of the trailing edge after crossing the endothelium. The role of Sharpin in the early steps of granulocyte transmigration has remained unknown. However, in this thesis, using intravital real‐time imaging experiments on postcapillary veins in the cremaster muscles of wild‐type (wt) and Sharpin‐deficient mice (Sharpindeficient mice, hereafter also called Sharpincpdm or Sharpin lacking mice), I showed that Sharpin deficient granulocytes are unable to switch from fast rolling to slow rolling and to firmly adhere, thus showing that Sharpin regulates the early steps of transmigration as well.

Mahdollinen onkogeeni Sharpin: molekulaarinen kartoitus ja toiminnallisten sitoutumiskumppaneiden karakterisaatio Sharpiini (SHANK‐Associated RH Domain Interactor) proteiini toimii monissa solun prosesseissa tuomalla eri proteiineja yhteen samaan kompleksiin. Sitoutuessaan eri proteiineihin, sharpiini säätelee niiden aktiivisuutta. Sharpiini on mm. tärkeä osa NF‐ κB:n aktivaatiota ohjaavassa LUBAC kompleksissa. Sen lisäksi sharpiini estää sitoutuessaan PTEN:n, integriinien, T solu reseptorin ja kaspaasi‐1:n toimintaa. Väitöskirjatyössäni olen selvittänyt sharpiinin interaktomin, proteiinit, joihin sharpiini sitoutuu. Selvittämällä interaktomin, löysin uusia solun signalointireittejä, joiden säätelyyn sharpiini osallistuu. Samalla vahvistin sharpiinin ja Arp2/3‐kompleksin interaktion. Osoitin, että sharpiinin sitoutuminen Arp2/3‐kompleksiin on tärkeää liikkuvan solun etureunan, lamellipodian, muodostumiselle ja liikkumiselle. Väitöskirjani toinen osatyö osoittaa, että leukosyyteissä sharpiinin puutos häiritsee leukosyyttien kulkemisnopeuden säätelyä ja kiinnittymistä muihin soluihin. Tämän tuloksen perusteella voidaan olettaa, että sharpiinilla on tärkeä tehtävä leukosyyttien ekstravasaation alkuvaiheessa. On todennäköistä, että tämä vaikuttaa immuunipuolustuksen toimintaan.